2018
DOI: 10.1021/acs.biochem.8b00333
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Activates β-Cell Glucokinase by Promoting Formation of the “Glucose-Activated” State

Abstract: The release of insulin from the pancreas is tightly controlled by glucokinase (GCK) activity that couples β-cell metabolism to changes in blood sugar. Despite having only a single glucose-binding site, GCK displays positive glucose cooperativity. Ex vivo structural studies have identified several potential protein conformations with varying levels of enzymatic activity, yet it is unclear how living cells regulate GCK cooperativity. To better understand the cellular regulation of GCK activation, we developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 69 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…[133] As GLP-1 is known to potentiate GSIS at physiologically intermediate (8-11 mM) glucose concentrations [134], it seems likely that this insulinotropic effect is achieved, in part, by promoting S-nitrosylation of GCK. [133] A recent report also demonstrated that chemically-mediated S-nitrosylation activates GCK by promoting the highly active closed GCK conformation [135], much like α-type activating mutations [40], small molecule GKAs [15,16,117], and high glucose concentrations. Despite these results, the direct influence that granular association and S-nitrosylation have on GCK activity remain incompletely understood.…”
Section: Sequestration At the Periphery Of Insulin Granules And S-nitmentioning
confidence: 99%
“…[133] As GLP-1 is known to potentiate GSIS at physiologically intermediate (8-11 mM) glucose concentrations [134], it seems likely that this insulinotropic effect is achieved, in part, by promoting S-nitrosylation of GCK. [133] A recent report also demonstrated that chemically-mediated S-nitrosylation activates GCK by promoting the highly active closed GCK conformation [135], much like α-type activating mutations [40], small molecule GKAs [15,16,117], and high glucose concentrations. Despite these results, the direct influence that granular association and S-nitrosylation have on GCK activity remain incompletely understood.…”
Section: Sequestration At the Periphery Of Insulin Granules And S-nitmentioning
confidence: 99%
“…Nitric oxide through S -nitrosylation of glucokinase (at cysteine-371) and syntaxin 4 (at cysteine-141) facilitates GSIS (Rizzo and Piston, 2003[ 105 ]; Wiseman et al, 2011[ 134 ]; Kruszelnicka, 2014[ 65 ]; Seckinger et al, 2018[ 113 ]). Using quantitative imaging of multicolor fluorescent proteins fused to glucokinase, it has been demonstrated that the dynamic association of glucokinase with secretory granules is modulated by NO (Rizzo and Piston, 2003[ 105 ]).…”
Section: Nitric Oxide and The Endocrine Pancreasmentioning
confidence: 99%
“…Indeed, insulin is found to stimulate NO production leading to S -nitrosylation of glucokinase in cultured β-cells (βTC3 cells); moreover, inhibition of NOS disrupts glucokinase association with secretory granules and glucokinase conformation (Rizzo and Piston, 2003[ 105 ]). It has been demonstrated that elevated glucose and S -nitrosylation, both induce the same high-activity glucokinase conformational state I in βTC3 cells (Seckinger et al, 2018[ 113 ]). Ultimately, attachment of a nuclear localization signal sequence to NOS in βTC3 cells drives glucokinase to the nucleus in addition to its normal cytoplasmic and granule targeting (Rizzo and Piston, 2003[ 105 ]).…”
Section: Nitric Oxide and The Endocrine Pancreasmentioning
confidence: 99%
“…Classic “molecular switch” type sensors, such as the Protein Kinase A activity reporters (AKARs) that contain both external sensing domains and internal effector-binding domains, have been converted to homotransfer reporters in four different colors [34]. Sensors that report changes in a full sequence protein, like myosin light chain kinase (MLCK) [34] or glucokinase [56], have also been successfully converted to FLAREs.…”
Section: Biosensor Designmentioning
confidence: 99%